History from the Bottom Up & The Inside Out Ethnicity, Race, and Identity in Working-Class History - Barrett, James R. (Duke University Press, 2017)
History from the Bottom Up and the Inside Out James R. Barrett rethinks the boundaries of American social and labor history by investigating the ways in which working-class, radical, and immigrant people's personal lives intersected with their activism and religious, racial, ethnic, and class identities. Concerned with carving out space for individuals in the story of the working class, Barrett examines all aspects of individuals' subjective experiences, from their personalities, relationships, and emotions to their health and intellectual pursuits. Barrett's subjects include American communists, "blue-collar cosmopolitans"-such as well-read and well-traveled porters, sailors, and hoboes-and figures in early twentieth-century anarchist subculture. He also details the process of the Americanization of immigrant workers via popular culture and their development of class and racial identities, asking how immigrants learned to think of themselves as white. Throughout, Barrett enriches our understanding of working people's lives, making it harder to objectify them as nameless cogs operating within social and political movements. In so doing, he works to redefine conceptions of work, migration, and radical politics.